2010
DOI: 10.2967/jnumed.109.068775
|View full text |Cite
|
Sign up to set email alerts
|

CT Hounsfield Units of Brown Adipose Tissue Increase with Activation: Preclinical and Clinical Studies

Abstract: Brown adipose tissue (BAT) densities assessed as CT Hounsfield units (HUs) were evaluated in a rodent model and in patients to determine whether HUs changed in relation to BAT activity. Methods: Serial 18 F-FDG PET/CT was performed on rats under both room temperature control conditions and after 4 h of coldstimulation, which is known to activate BAT. The maximum standardized uptake values and CT HUs of BAT were measured, and tissues were examined in the laboratory. Image records from cancer patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
184
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(202 citation statements)
references
References 14 publications
12
184
4
2
Order By: Relevance
“…The lower radiodensity of the BAT in the overweight age-matched control subjects and in the participants with type 2 diabetes could suggest a similar shift toward lipid storage or a lipolytic dysfunction. BAT glucose uptake appears to be significantly influenced by BAT TG content (5,33). Despite these observations, our results do not suggest impairment in intracellular TG lipolysis in BAT or WAT in individuals with type 2 diabetes because the cold-induced reduction in BAT radiodensity and systemic NEFA turnover were the same compared with young healthy individuals.…”
Section: Discussioncontrasting
confidence: 71%
“…The lower radiodensity of the BAT in the overweight age-matched control subjects and in the participants with type 2 diabetes could suggest a similar shift toward lipid storage or a lipolytic dysfunction. BAT glucose uptake appears to be significantly influenced by BAT TG content (5,33). Despite these observations, our results do not suggest impairment in intracellular TG lipolysis in BAT or WAT in individuals with type 2 diabetes because the cold-induced reduction in BAT radiodensity and systemic NEFA turnover were the same compared with young healthy individuals.…”
Section: Discussioncontrasting
confidence: 71%
“…Although the present study was not designed to investigate the mechanisms underlying the association between adipose tissue mean attenuation and fat cell weight, we speculate that increased organelle content of small fat cells per surface unit could possibly explain why they show greater mean attenuation. Baba et al 17 demonstrated that brown adipose tissue mean attenuation increased under activated conditions following a decrease in lipid content. Furthermore, Hu et al 11 observed that HUs of brown adipose tissue were more positive than those of white adipose tissue and speculated that brown adipocyte characteristics could account for this difference as they contain more non-lipid components and are more vascularized and innervated than white adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In computed tomography (CT) and 1 H MRI studies, fat fraction measurements are used to differentiate the highly hydrated brown adipose tissue from the less hydrated normal white adipose tissue (WAT) (13)(14)(15). Unfortunately, human BAT is a heterogeneous mixture of white and brown adipocytes (16), and partial volume effects that arise from the limited spatial resolution of these imaging modalities make these types of measurements unreliable and nonspecific.…”
Section: Fdg-petmentioning
confidence: 99%